2019
DOI: 10.1016/j.dib.2019.104127
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional non-destructive testing data maps for reinforced concrete slabs with simulated damage

Abstract: This research presents the use of a total of five Non-Destructive Testing Techniques (NDTs) and their combination to detect and quantify subsurface simulated defects in Reinforced Concrete slabs. The NDT techniques were applied on a total of nine 1800 mm × 460 mm reinforced concrete slabs with varying thicknesses of 100 mm, 150 mm and 200 mm. Contour data maps from each technique were prepared. This Data article presents the Non-Destructive Testing Techniques’ specifications, experimental set-up and converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Similar studies were carried out by scientists in the study [4]. In this work, combinations of various methods of non-destructive testing of reinforced concrete slabs were used.…”
Section: Introductionmentioning
confidence: 93%
“…Similar studies were carried out by scientists in the study [4]. In this work, combinations of various methods of non-destructive testing of reinforced concrete slabs were used.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies demonstrated that the scattering attenuation of shear waves is less significant at frequencies lower than 50 kHz for commonly used aggregate of size 15 mm in concrete. As such, by using current UPE devices, concrete can be treated as a homogeneous medium with a single constant shear-wave velocity, and the standard SAFT is employed in the UPE equipment to detect voids, imperfections, and defects in concrete structures [22][23][24][25][26][27][28][29][30]. Ref.…”
Section: 𝑍 = 𝐶mentioning
confidence: 99%